The Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) Versi Indonesia: Studi Pendahuluan Uji Validitas Dan Reliabilitas Pada Ibu Hamil - Yuliani, Diki Retno; Aini, Fajaria Nur; Winarso, Septerina Purwandani; Amalia, Riza (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2023)
Breastfeeding self-efficacy is one thing that can influence breastfeeding success. The aim of this study was to test the validity and reliability of the breastfeeding self-efficacy scale short form (BSES-SF) in Indonesian for pregnant women. The sample was 91 third trimester pregnant women in Banyumas Regency taken in 2022 using cluster sampling. The BSES-SF consists of 14 question items with a Likert scale of 1 (not very confident) to 5 (always confident). Data analysis to assess construct validity through factor analysis and internal reliability (internal consistency). The results obtained have a loading factor value of 0.5, the Indonesian version of the BSES-SF is valid for use in the population of pregnant women in Indonesia, the Indonesian version of the BSES-SF has a good internal reliability value (internal consistency), Cronbach's alpha 0.917 and Cronbach's Alpha if value item deleted from 14 items 0.90. So the Indonesian version of the BSES-SF is valid and reliable to use in the population of pregnant women in Indonesia.